A chronopharmacological comparison of ciprofol and propofol: focus on sedation and side effects - Li, Xuehan; Yang, Xinqing; Chen, Chen; Yu, Ziqing; Wang, Houping; Liu, Ruixue; He, Jianrong; Shu, Bin; Duan, Guangyou; Zhang, Erquan; Ju, Dapeng; Huang, He (Frontiers in Molecular Neuroscience, 2025)
Propofol is a commonly used intravenous anesthetic in clinical practice, while ciprofol, a propofol derivative, also targets GABAA receptors with enhanced anesthetic potency. Regarding chronopharmacology, it remains unclear whether the new drug ciprofol has improved anesthetic effect and less side effects compared with propofol. First, we assessed the critical anesthetic dosage (Dca) of ciprofol and propofol exhibited diurnal rhythmicity. At the highest Dca, the loss of righting reflex duration was significantly longer for ciprofol than that for propofol at both Zeitgeber Time (ZT) 4 and ZT16. The β3 subunits of the GABAA receptor, which are involved in mediating anesthetic effects, and the metabolizing enzyme UGT1A9 for propofol demonstrated rhythmic expression. Moreover, molecular dynamics simulation indicated a higher binding affinity of R-ciprofol to GABRB3 compared with propofol. Animal behavior experiments indicated that ciprofol was associated with no incidence of side effects at any time of day, while propofol exhibited circadian-related adverse effects. Notably, ciprofol infrequently disrupted the rhythmicity of clock gene expression compared to propofol. From a chronopharmacological perspective, ciprofol offers improved sedation and fewer side effects compared to propofol, suggesting its higher potential for clinical application.